Using ChatGPT to Overcome Writer’s Block: A Study of Non-native English Students (Siddhajyoti Interdisciplinary Journal, 2026)
This qualitative study investigates the effectiveness of ChatGPT to overcome writer’s block among English language researchers, focusing on how it enhances academic writing when it is used ethically. The research was conducted among three university-level students and researchers. The researcher adopted a purposeful sampling technique. The research participants shared their insights through online unstructured interviews. The findings revealed that the latest emerged AI tool has definitely provided a wide range of support and benefits, unblocking the ideas among non-native English students. Participants showed their regard for AI’s support by providing immediate feedback; however, excessive reliance on AI tools not only destroys the creativity and critical thinking of researchers but also the originality of writing. Participants also expressed concerns about the potential of replacing human beings with AI. This study highlighted the need for a balanced approach to integrating AI and offering professional training for educators and learners on the ethical application of AI tools.